PENGARUH MOTIVASI BELAJAR TERHADAP MATA PELAJARAN FIQIH SISWA KELAS VII MTS SALAFIYAH SYAFI’IYAH TEBUIRENG JOMBANG - Defan Sony Darmawan; Solihul Anshori (JURNAL ILMIAH NUSANTARA, 2025)
Motivation is one of the important factors that influence learning. Someone who has high motivation tends to devote all their abilities to get optimal learning achievement. The strength and weakness of each individual's motivation are different, it is influenced by internal and external factors. This study aims to find out and analyze the influence of Learning Motivation on Fiqh Subjects of Class VII Students of Mts Salafiyah Syafi'iyah Tebuireng Diwek Jombang. Quantitative approach with ex post facto research type which took place at MTs Salafiyah Syafi'iyah Tebuireng. The data collection technique used was by collecting data from questionnaires and report cards. The sample in this study was 55 students as respondents, using probability sampling using simple random sampling techniques and using data analysis techniques with simple linear regression tests. The influence of Motivation on Fiqh Subjects of Salafiyah Syafi'iyah Tebuireng students in understanding fiqh material is very significant. This is indicated by the significance value of the F test of 0.005, which is less than 0.05, so Ho is rejected and HA is accepted. In addition, the calculated F value of 8.855 is greater than the F table value (3.23), which also supports the conclusion that there is a significant influence.